Hypotensive and sedative effects of α-adrenoceptor agonists: relationship to α1- and α2 -adrenoceptor potency - Clough, D.P. (1981)
1 The purpose of this study was to investigate whether the separation between the hypotensive and sedative effects of a new series of centrally acting antihypertensive drugs was due to differences between the relative pre-junctional (α(2)) and post-junctional (α(1)) adrenoceptor agonist properties of the compounds. 2 In anaesthetized rats the intravenous doses of clonidine, ICI 101187, ICI 106270, ICI 109683 and ICI 110802 required to lower blood pressure (BP) by 20 mm Hg were 1.2, 5.1, 5.5, 3.3 and 5.4 μg/kg respectively. 3 In a test for sedation, ICI 101187 had at least 10 times less sedative effect than clonidine, ICI 106270 and ICI 109683 had at least 30 times less sedative effect than clonidine while ICI 110802 was not active. In a locomotor activity test the intravenous dose of clonidine required to reduce activity by 50% was 15.3 μg/kg, for ICI 101187 it was 194, for ICI 106270 it was 238 and for 110802 it was 313 μg/kg. 4 In the pithed rat the ED(50)s of clonidine, ICI 101187, ICI 106270, ICI 109683 and ICI 110802 as α(2)-agonists were 19.4, 9.3, 63.2, 43.0 and 78.5 μg/kg respectively. The α(1)-adrenoceptor potencies were quite similar for the five drugs and varied between 3.2 μg/kg for ICI 110802 and 8.7 μ/kg for ICI 106720. Potency as α(2)-adrenoceptor agonists was also assessed in the mouse vas deferens. Clonidine and ICI 101187 were similar in potency with IC(50)s of 9.3 × 10(-9)m and 8.9 × 10(-9)m respectively. ICI 106270 and ICI 110802 were much weaker with IC(50)s of 4.9 × 10(-8)m and over 5.7 × 10(-8)m respectively. 5 Since all the compounds had similar potencies as α(1)-agonists, this could not explain their different sedative effects. The weakest compounds as sedatives were also weakest as α(2)-agonists, although ICI 101187 which was as potent as clonidine as an α(2)-agonist was still 10 times weaker as a sedative. 6 Hypotensive activity appears to be more closely related to α(1)- than to α(2)-potency. 7 Clonidine was more potent as both a sedative and a hypotensive agent than would be predicted from its activity at either the α(1)- or the α(2)-adrenoceptor.